Hierarchically porous and nitrogen, sulfur-codoped graphene-like microspheres as a high capacity anode for lithium ion batteries. Issue 11 (2nd January 2015) - Sun, Dongfei; Yang, Juan; Yan, Xingbin
Abstract : The novel hierarchically porous and nitrogen, sulfur-codoped graphene-like microspheres are constructed as the anode material for lithium ion batteries. High surface area and efficient heteroatom doping provide high capacity and enhanced cycling stability. Abstract : Novel hierarchically porous and nitrogen, sulfur-codoped graphene-like microspheres (3D NS-GSs) are synthesized using Ni microspheres as the template and using poly(vinylpyrrolidone) and (NH4 )2 S2 O8 as the carbon and nitrogen precursor, respectively. As an anode material in lithium ion batteries, the 3D NS-GS electrode displays a superior capacity with excellent cycling stability.